LC-MS Analysis, 15-Lipoxygenase Inhibition, Cytotoxicity, and Genotoxicity of Dissotis multiflora (Sm) Triana (Melastomataceae) and Paullinia pinnata Linn (Sapindaceae) - Alian Désiré Afagnigni; Maximilienne Ascension Nyegue; Steve Valdi Djova; François-Xavier Etoa (Journal of Tropical Medicine)
This study aims to evaluate the anti-inflammatory, cytotoxicity, and genotoxicity activities of Dissotis multiflora (Sm) Triana and Paullinia pinnata Linn used traditionally in Cameroon to treat infectious diseases. Phytochemical screening was carried out using the LC-MS procedure. The ferrous oxidation-xylenol orange (FOX) assay was used to determine the 15-lipoxygenase (15-LOX) inhibitory activity of the plant samples. The tetrazolium-based colorimetric (MTT) assay was performed using Vero cells. The Ames test was carried out using Salmonella typhimurium TA98 and TA100 tester strains. LC-MS chromatogram of D. multiflora led to the identification of four known compounds, namely, 5-(3,5-dinitrophenyl)-2H-tetrazol (2), 2,2'-{[2-(6-amino-9H-purine-9-yl)ethyl]imino}diethanol (14), 1,2,5-oxadiazolo [3,4-b]pyrazine, 5,6-di (3,5-dimethyl-1-piperidyl) (19), and nimbolinin D (20) while four compounds were also identified in P. pinnata known as 2-hydroxycarbamoyl-4-methyl-pentanoic acid (2), pheophorbide A (16), 1-[4-({2-[(1-methyl-1H-indol-5-yl)amino]-4-pyrimidinyl}oxy)-1-naphthyl]-3-[1-(4 methylphenyl)-3-(2-methyl-2-propanyl)-1H-pyrazol-5-yl]urea (17), and nimbolinin D (18). D. multiflora and P. pinnata inhibited 15-LOX activity in concentration-dependent manner. The LC50 (concentration that kills 50% of cells) values of the extracts ranged from 0.13 ± 00 to 1 ± 00 mg/mL for P. pinnata and D. multiflora, respectively. P. pinnata was cytotoxic at concentrations tested while D. multiflora was not. The selectivity index (SI) values ranged from 0.16 to 10.30 on Vero cell lines. No genotoxic effect was observed against both strains tested. These extracts are sources of compounds which can be used to control infectious diseases and associated inflammation. However, caution should be taken while using P. pinnata for medicinal purposes.